2023
DOI: 10.3390/photonics10020129
|View full text |Cite
|
Sign up to set email alerts
|

One-Pixel Attack for Continuous-Variable Quantum Key Distribution Systems

Abstract: Deep neural networks (DNNs) have been employed in continuous-variable quantum key distribution (CV-QKD) systems as attacking detection portions of defense countermeasures. However, the vulnerability of DNNs leaves security loopholes for hacking attacks, for example, adversarial attacks. In this paper, we propose to implement the one-pixel attack in CV-QKD attack detection networks and accomplish the misclassification on a minimum perturbation. This approach is based on the differential evolution, which makes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…What is worse is that recent studies have shown that adversarial attacks can be applied to the real world by those possessing ulterior motivates, which pose a serious threat to areas requiring high information security, for example, autonomous driving [ 26 ]. Similarly, for the CVQKD system using neural networks for attack detection and classification, adversarial attacks can also affect the CVQKD system, which is proved by our simulation experiments [ 27 ].…”
Section: Introductionmentioning
confidence: 66%
“…What is worse is that recent studies have shown that adversarial attacks can be applied to the real world by those possessing ulterior motivates, which pose a serious threat to areas requiring high information security, for example, autonomous driving [ 26 ]. Similarly, for the CVQKD system using neural networks for attack detection and classification, adversarial attacks can also affect the CVQKD system, which is proved by our simulation experiments [ 27 ].…”
Section: Introductionmentioning
confidence: 66%
“…Input: input data X, perturbation ε, number of data N, attack type D, parameter θ, λ Initialization: θ, λ and ε For i ← 0 to N do (x i , y i ) ∼ X // Sampling from normal distribution x * i ← G(O(x i ), y LL , ε) // Construct adversarial samples through ( 14) and ( 15) Get the adversarial loss function through (13) θ ← θ − η • ∇ θ (Loss(θ)) // Update network parameters Get θ of the generative network G through (11) Train APE-GAN through (12) End for Output: generator D…”
Section: Algorithm 1 Improved Ape-gan Algorithmmentioning
confidence: 99%
“…However, real continuous-variable quantum key distribution (CVQKD) [3][4][5][6] systems face security vulnerabilities due to some deviations between the theoretical assumptions and the implementation, which gives Eve the opportunity to compromise security by stealing information from legitimate parties. The eavesdroppers can employ wavelength attacks [7,8], calibration attacks [9,10], local-oscillation (LO) intensity attacks [11], homodyne-detector-blinding attacks [12], saturation attacks [13], and other attack strategies to compromise the safety of the GMCS CV-QKD. The major idea of these practical attack strategies is to use optical device flaws to deviate from the redundant noise estimates, while the essence of the corresponding typical countermeasures is to incorporate suitable real-time monitoring modules or measurement devices into the system, which depends considerably on the accuracy of the estimated excess noise.…”
Section: Introductionmentioning
confidence: 99%
“…Research on ML-assisted quantum attacks [32,33], attack detection and prevention [27,[34][35][36][37][38][39][40], and methods for hacking ML-based attack prevention strategies [41,42] is not included in this survey. Huang, Liu, and Zhang [43] have previously reviewed the literature in this area.…”
Section: Introductionmentioning
confidence: 99%
“…Huang, Liu, and Zhang [43] have previously reviewed the literature in this area. We note that [33,[37][38][39][40][41][42] were published after [43] so were not included in their review. Further, this survey does not include works on ML for quantum communication in general, only addressing works specifically on the application of CV-QKD.…”
Section: Introductionmentioning
confidence: 99%